Enabling Transparent‐Conductive‐Oxide Free Efficient Heterojunction Solar Cells by Flexibly Using Dopant‐Free Contact. (19th July 2022) - He, Jian; Wang, Genshun; Qiu, Yibin; Tang, Zeguo; Ye, Fan; Zhang, Chaohua; Wang, Shulin; Cai, Lun; Yu, Tianbao; Gao, Pingqi
Abstract: Minimizing the optical parasitic absorption loss in hydrogenated amorphous silicon (a‐Si:H) and transparent conductive oxide (TCO) layers is considered an effective approach to further improve the power conversion efficiencies (PCEs) of crystalline silicon heterojunction (SHJ) solar cells. In this work, carrier‐selective passivating contacts for both polarities, e.g., alkali fluoride/aluminum electron‐selective contact and transition metal oxide/silver hole‐selective contact, are used to completely replace the doped a‐Si:H layers in SHJ solar cell, forming a totally TCO‐ and dopant‐free asymmetric structure. By minimizing the charge carrier transporting and recombination losses on the front‐side electron‐selective contact through interface engineering, an improved photovoltaic performance with a short‐circuit current density of 40.5 mA cm −2, an open‐circuit voltage of 0.709 V, and a fill factor of 79.6% is realized, resulting in a final PCE exceeding 22.9%. The successful demonstration of this work provides an effective way to further boost the efficiency, as well as reduce the cost of SHJ solar cells with a TCO‐free and doped a‐Si:H‐free configuration, using a moderate and simplified fabrication process. Abstract : Transparent conductive oxide‐ and dopant‐free asymmetric structured crystalline silicon heterojunction solar cells are designed to minimize the optical parasitic absorption losses by using rubidium fluoride/aluminum electron‐selective contact and molybdenum oxide/silver hole‐selective contact. Combined with the use of a thin titanium oxide interlayer to passivate the electron‐selective contact interface, an efficiency of 22.9% is realized.